Game 2D untuk Melatih Daya Ingat dan Konsentrasi Anak Menggunakan Construct 2 - Ardianto, Doni Wahyu, Umi Fadlillah, S.T. M.Eng (2016)
Stimulating the brain's performance is necessary in early childhood, because intelligence is related to brain growth and development. Intelligence capacity, 50% occur when children aged 4-6 years, 80% at age 8 years and its culmination at the age of 18 years. To optimize brain function needed good nutrition, adequate stimulation, and the degree of good health. Moving, activity and physical exercise through games method is one way to stimulate the brain. This study aims to make an application as media interactive learning games to train memory and concentration of children at an early age. This application is expected to assist educators in delivering learning materials. The design of the study were made using the game engine with Construct 2 HTML5-based data processing using visual effects features as well as setting event and action on each layout. In this game application will display a description of the first layout endemic in Indonesia, after which it will be displayed guess the picture to break up the concentration of users, and will show some quiz questions to be answered. Based on testing conducted at SD Negeri 1 Matesih can be concluded that 92% of teachers said this game makes children more enthusiasm for learning and 99% of children like this game.